Role of C4 carbon fixation in Ulva prolifera, the macroalga responsible for the world’s largest green tides - Liu, Dongyan; Ma, Qian; Valiela, Ivan; Anderson, Donald M.; Keesing, John K.; Gao, Kunshan; Zhen, Yu; Sun, Xiyan; Wang, Yujue (Communications biology, 2020)
Most marine algae preferentially assimilate CO 2 via the Calvin-Benson Cycle (C 3 ) and catalyze HCO 3 − dehydration via carbonic anhydrase (CA) as a CO 2 -compensatory mechanism, but certain species utilize the Hatch-Slack Cycle (C 4 ) to enhance photosynthesis. The occurrence and importance of the C 4 pathway remains uncertain, however. Here, we demonstrate that carbon fixation in Ulva prolifera , a species responsible for massive green tides, involves a combination of C 3 and C 4 pathways , and a CA-supported HCO 3 − mechanism. Analysis of CA and key C 3 and C 4 enzymes, and subsequent analysis of δ 13 C photosynthetic products showed that the species assimilates CO 2 predominately via the C 3 pathway, uses HCO 3 − via the CA mechanism at low CO 2 levels, and takes advantage of high irradiance using the C 4 pathway. This active and multi-faceted carbon acquisition strategy is advantageous for the formation of massive blooms, as thick floating mats are subject to intense surface irradiance and CO 2 limitation. Liu et al. present evidence that carbon fixation in Ulva prolifera takes place via a combination of C 3 and C 4 pathways in combination with the enzyme carbonic anhydrase. The active and multi-faceted carbon acquisition strategy in U. prolifera is advantageous for the formation of massive blooms as the thick floating mats are subject to intense surface irradiance and CO 2 limitation.